Employee turnover as a factor in the optimization of HR processes - Skowron-Mielnik, Beata; Gołembski, Marcin (Rotacja pracowników jako czynnik optymalizacji procesów kadrowych, 2019)
This article discusses employee turnover and the need to retain employees. Both issues are important for ensuring the appropriate number of employees and stable performance levels. Taking into account the current situation on the Polish labor market, employee turnover is a phenomenon nowadays more often induced by the employees themselves rather than by the organization for which significant workforce fluctuation generates the risk of increased costs of recruitment and decline in performance (in terms of quantity and quality). Consequently, a systematic analysis of the level of employee turnover and its causes are of key importance, in particular in terms of the organization’s actions aimed at reducing it. Therefore, the research problem addressed in the article is to identify the role of the personnel function and processes implemented as part of it in minimizing or intensifying the external, negatively perceived employee turnover. The empirical part of the research is based on an analysis of case studies of 11 enterprises
Management Forum, 2019, vol. 7, no. 1, s. 8-13
Keywords: employee turnover; HR processes; personnel function; rotacja pracowników; procesy kadrowe; funkcja personalna